KECERDASAN QALBIYAH DALAM PERSPEKTIF PSIKOLOGI ISLAM - Syamsu Nahar (Al-Irsyad: Jurnal Pendidikan dan Konseling, 2016)
Intelligence is one great gift from Allah to man and made him one of thehuman advantages compared to other creatures. With his intelligence especiallyintelligence of qalbiyah, humans can be continuously maintain and improvethe quality of life is increasingly complex, through a process of thinking andlearning continuously. Prophet Muhammad confirms that the essence of aperson is dependent on the condition of the heart (good or bad man is determinedby the heart.Keywords: Kecerdasan Qalbiyah, Psikologi Islam.